Effect of Digital Transformation in Customers’ Experience in Banking - Chhetri, Ashmita Dahal; Aryal, Khimananda (Jana Adarsha Research Journal, 2025)
This research examines how the banking industry’s digital revolution has affected consumers’ experiences, with a particular emphasis on important elements including ease of use, speed, flexibility, and convenience. The research provides a thorough analysis by combining quantitative data from 172 respondents with quantitative insights from survey using both descriptive and causal-comparative research techniques. The results show that although customers prefer features like 24/7 access and customization, digital banking services are generally well-received, however opinions on their efficacy differ. The results of the regression analysis demonstrate that the independent variables (convenience, simplicity, flexibility, and time management) and customer experience are significantly correlated, with flexibility exhibiting the largest positive connection. Nonetheless, it seems that customer experience and simplicity are inversely correlated, indicating that excessively simplified procedures may lower satisfaction. These findings notwithstanding, several factors, such “Time Manner” and “Convenience,” did not substantially affect the customer experience, suggesting areas in need of more study. Overall, the study emphasizes how important digital transformation is to improving the banking customer experience, but it also emphasizes how constant development is required to keep up with changing customer expectations.